2004
DOI: 10.1074/jbc.m311849200
|View full text |Cite
|
Sign up to set email alerts
|

A Cypher/ZASP Mutation Associated with Dilated Cardiomyopathy Alters the Binding Affinity to Protein Kinase C

Abstract: Dilated cardiomyopathy is characterized by ventricular dilation with systolic dysfunction of cardiac muscle. Recent genetic studies have revealed that mutations in genes for cytoskeleton proteins distributed in the Z-disc and/or intercalated discs of the cardiac muscle are major predictors of cardiomyopathy. However, as mutations in these genes can account for only a part of the patient population, there should be another diseasecausing gene(s) for cardiomyopathy. Cypher/ZASP appears to be an ideal candidate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 40 publications
6
84
0
3
Order By: Relevance
“…Because of splice variants, not all exons are transcribed in cardiac and skeletal muscles, and 3 transcripts appear in skeletal muscle [16]. Exon 15 is present only in the 2 long transcripts; the mutation in exon 15 (D626N) increases the affinity of the LIM domain for protein kinase C [27]. The novel mutation described here is found in a highly evolutionarily conserved domain in exon 15.…”
Section: Discussionmentioning
confidence: 89%
“…Because of splice variants, not all exons are transcribed in cardiac and skeletal muscles, and 3 transcripts appear in skeletal muscle [16]. Exon 15 is present only in the 2 long transcripts; the mutation in exon 15 (D626N) increases the affinity of the LIM domain for protein kinase C [27]. The novel mutation described here is found in a highly evolutionarily conserved domain in exon 15.…”
Section: Discussionmentioning
confidence: 89%
“…Cypher mutations were first identified in patients with human familial and sporadic dilated cardiomyopathy (Arimura et al 2004, Vatta et al 2003, a disease that has been linked to the disruption of the cytoskeletal architecture (Vatta et al 2003). Mutations were identified in several domains within Cypher/ZASP, and found to be associated with a spectrum of different diseases.…”
Section: A Role For Cypher In Human Muscle Diseasementioning
confidence: 99%
“…A mutation in exon 2 (V55I), which is common to all isoforms, was independently shown to be associated with INLVM in a Japanese population (Xing et al 2006, Figure 2). Other independent studies identified Cypher/ZASP mutations (D626N) in a long isoform-specific exon (exon 15; within the third LIM domain) in Japanese patients exhibiting familial DCM and INLVM (Arimura et al 2004, Xing et al 2006, Figure 2). (Arimura et al 2004).…”
Section: A Role For Cypher In Human Muscle Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…1). A mutation in the third LIM domain of Cypher causes dilated cardiomyopathy and increases Cypher affinity for PKC compared with the wild type protein, demonstrating the importance of PKC recruitment in vivo (Arimura et al, 2004). Apart from Enigma family proteins, other Z-disk-associated proteins were identified as potential anchors of PKC.…”
Section: The Z-disk As a Focal Point For Force Propagationmentioning
confidence: 99%